History education 101 : the past, present, and future of teacher preparation - Warren, Wilson J.; Cantu, D. Antonio (Emerald Publishing Limited : IAP, 2008)
Historians and teacher educators nationwide are now engaged in discussions about the importance of history teacher preparation. Interest within the history profession about the teaching of K-12 history has increased significantly during the past two decades, particularly since the controversy over the National Standards for History's publication. This attention is evident not only in the historical professions' various publications, but also in the federal government's multi-million dollar Teaching American History Program and the No Child Left Behind Act. Professional historians are increasingly committed to improving the teaching of history at the K-12 level through many forms of collaboration.History Education 101's thirteen essays are organized into three sections: context, practice, and new directions. The essays' contributors, tenured faculty who teach history teaching methods courses in colleges and universities throughout the United States, focus on how history education has, is, and will be taught to new K-12 teachers throughout the United States. Perhaps more than ever, it is critical for Americans to understand the role of higher education in the preparation of future middle and high school history teachers. This book provides important insights for academics in history and education departments as well as other individuals who are concerned with the status and improvement of history teaching in the schools, particularly current and future elementary and secondary teachers and administrators.